Prospects for New England Agriculture: Farm to Fork. (December 2019) - Werner, Samantha; Lemos, Scott R.; McLeod, Amanda; Halstead, John M.; Gabe, Todd; Huang, Ju-Chin; Liang, Chyi Lyi; Shi, Wei; Harris, Lily; McConnon, James
Abstract: This paper summarizes a multi-state, multi-year study assessing the potential for local agriculture in northern New England. While largely rural, this region's agricultural sector differs greatly from the rest of the United States, and demand for locally produced food has been increasing. To assess this unique economic landscape, researchers and Cooperative Extension at the Universities of Maine, New Hampshire, and Vermont investigated four key areas: (1) local food capacities, (2) constraints to agricultural expansion, (3) consumer preferences for local and organic produce, and (4) the role of intermediaries as alternative local food outlets. The project included input from local farmers, Extension members, restaurants, and the general public. We present the four research areas in a sequential, overlapping fashion. The timing of our research was such that each step in the process informed the next and can be used as a template for assessing a region's potential for local agricultural production.